Implementation of image-guided brachytherapy (IGBT) for patients with uterine cervix cancer: a tumor volume kinetics approach - Carvalho, Heloisa de Andrade; Mendez, Lucas Castro; Stuart, Silvia Radwanski; Guimarães, Roger Guilherme Rodrigues; Ramos, Clarissa Cerchi Angotti; Paula, Lucas Assad de; Sales, Camila Pessoa de; Chen, André Tsin Chih; Blasbalg, Roberto; Baroni, Ronaldo Hueb (Journal of Contemporary Brachytherapy, 2016)
Purpose : To evaluate tumor shrinking kinetics in order to implement image-guided brachytherapy (IGBT) for the treatment of patients with cervix cancer. Material and methods : This study has prospectively evaluated tumor shrinking kinetics of thirteen patients with uterine cervix cancer treated with combined chemoradiation. Four high dose rate brachytherapy fractions were delivered during the course of pelvic external beam radiation therapy (EBRT). Magnetic resonance imaging (MRI) exams were acquired at diagnosis (D), first (B1), and third (B3) brachytherapy fractions. Target volumes (GTV and HR-CTV) were calculated by both the ellipsoid formula (VE) and MRI contouring (VC), which were defined by a consensus between at least two radiation oncologists and a pelvic expert radiologist. Results: Most enrolled patients had squamous cell carcinoma and FIGO stage IIB disease, and initiated brachytherapy after the third week of pelvic external beam radiation. Gross tumor volume volume reduction from diagnostic MRI to B1 represented 61.9% and 75.2% of the initial volume, when measured by VE and VC, respectively. Only a modest volume reduction (15-20%) was observed from B1 to B3. Conclusions : The most expressive tumor shrinking occurred in the first three weeks of oncological treatment and was in accordance with gynecological examination. These findings may help in IGBT implementation.